Recommendations for Preventing Land Degradation Processes - Takhirov Kozim Najim ogli; Tajiyev Zafar Takhir ogli (Web of Journals Publishing, 2023)
In the article, land degradation, its causes, the status of the works being carried out to prevent these processes and, in turn, suggestions and recommendations are mentioned.
Keywords: Land degradation, land quality, agricultural land, pasture land, recultivation.